2016
DOI: 10.1002/pmic.201500344
|View full text |Cite
|
Sign up to set email alerts
|

State‐of‐the‐art housekeeping proteins for quantitative western blotting: Revisiting the first draft of the human proteome

Abstract: Western blotting (WB) analysis is the most popular and widely used methodology for protein detection and characterization over recent decades. In accordance with the advancement of the technologies for the acquisition of WB signals, a quantitative value is used to present the abundance of target proteins in a complex sample, thereby requiring the use of specific proteins as internal references that represent total proteins. Heretofore, proteins encoded by housekeeping genes such as GAPDH, β-tubulin and β-actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…There has been an extensive debate on which house-keeping proteins (HKPs) can be used as steady-level controls in molecular biology experiments (40). Recent research has shown that classic HKPs may actually change their expression under specific conditions (41). For example in our dataset, GAPDH, a popular HKP, exhibits stable levels for most treatments, but could not be a good control for studies with bortezomib and few other compounds (Fig.…”
Section: "Untouchable" Proteome Reflects Essential Cell Functionsmentioning
confidence: 96%
“…There has been an extensive debate on which house-keeping proteins (HKPs) can be used as steady-level controls in molecular biology experiments (40). Recent research has shown that classic HKPs may actually change their expression under specific conditions (41). For example in our dataset, GAPDH, a popular HKP, exhibits stable levels for most treatments, but could not be a good control for studies with bortezomib and few other compounds (Fig.…”
Section: "Untouchable" Proteome Reflects Essential Cell Functionsmentioning
confidence: 96%
“…However, stable expression under treatment conditions has not been studied for most of these proteins. Indeed, in practice, a number of these HKPs show inconsistent expression levels under different treatments (Vigelsø, Dybboe et al 2014;Janes 2015;Lee, Jo et al 2016). For example, GAPDH, one of the most extensively used HKPs showed variable expression in our compound panel especially for bortezomib ( Figure 31A).…”
Section: Untouchable Proteome Unravels House-keeping Proteinsmentioning
confidence: 99%
“…2d). Finally, we observed an association between the intensity of peptides from a housekeeping protein and the known proportion of human tissue in each sample (TAR DNA-binding protein 43 27 ; Fig. 2e).…”
Section: Resultsmentioning
confidence: 88%